The vital force - Square, Vicki Lambert, author; Orman, Jack L., advisor; Dietemann, David L., committee member; Dormer, James T., committee member; Kern, Sanford, committee member (Colorado State University. Libraries, 1980)
In a discussion of my work my inclination would be to focus in on my use of light. Most probably the reason for this is that using a strong light source, most often sunlight, is always a conscious decision in my work. In fact, I am not at all inclined to draw of that strong light is not present. The light in my work appears in one of two ways, or in combination. In some cases, particularly in the figures, the light appears as an opaque coating of the surface, describing volume as well as surface texture. In others, and these may be combined with the opaque quality, an atmospheric light pervades. This type of light establishes a space, but more importantly it creates the mood, or spirit if you will, by which the subject is enveloped. I am using light in a very conscious way, but the real forte of my work is the gestural, expressive, and strong line. The line is intuitive and is the very thread of continuity in my work. I believe I see things in terms of an active, dancing line enlivening the shadow, and therefore my line embodies movement. The line is what makes my work distinctive as corning from my hand. In terms of subject matter, my graduate exhibition is a most personal one. The progression of my artistic development and personal maturation is most evident in the self-portrait series. It goes from a beginning of a more superficial way of seeing myself and hiding things within me, to taking a hard and objective look desiring to lay bare hidden things; taking an unabashed look and not being afraid of what I see. Hands become an increasingly important part of my portrait. My hands are what I do things with, what I say things visually with, what I either hide or reveal with. Possibly they may be more expressive than the face, but together the hands and face constitute an undeniable force the viewer must deal with. I learn the most from doing the self-portrait, about the progression of my artwork. I believe I can go from the self-portrait to other subjects taking a fresh look, but always knowing the intensity of work that accompanies the understanding of the inner spirit of whatever subject I am dealing with. Most probably I will always return to the self-portrait to take new steps, to experiment, and to progress. I believe it to be a blessing to know concretely that I have a direction to always encounter an intense learning experience.
Keywords: Drawing; Light in art